2014
DOI: 10.4103/2249-4863.148109
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression in elderly population in the southern part of Punjab

Abstract: Background:Depressive symptoms are often not detected properly in elderly. The aim of this study was to explore the prevalence of depressive symptoms and possible co relational factors among elderly population.Materials and Methods:In a cross-sectional study, 100 elderly persons were screened. Geriatric depression scale (GDS) was used to assess depressive symptoms. A self-rating questionnaire was used to detect some sociodemographics and clinical variables.Results:100 respondents interviewed, 40 were 70 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
4
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 10 publications
4
24
4
3
Order By: Relevance
“…Contradictory to the findings as reported by majority of Indian studies no significant association was observed between education and employment status with depression. 11,14,15 In contrast to other studies no association was observed between depression and family composition. 10,16 …”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…Contradictory to the findings as reported by majority of Indian studies no significant association was observed between education and employment status with depression. 11,14,15 In contrast to other studies no association was observed between depression and family composition. 10,16 …”
Section: Discussioncontrasting
confidence: 53%
“…Similar findings were also reported in other studies. 10,11,13,14,16 However no such findings were observed by Kumar et al and Goyal et al 12,15 As reported by Sinha et al and Taqui et al those who were single (divorced, separated, widow, unmarried) were found to be more susceptible for depression. 13,16 But such type of findings was not reported in other studies.…”
Section: Discussionmentioning
confidence: 39%
See 2 more Smart Citations
“…This was in contrary with study report of Sengupta P 7 and some other authors 10,11 , in which they reported more statistically significant female preponderance. However no such findings were observed by Kumar et al 12 and Goyal et al 13 .…”
Section: Discussioncontrasting
confidence: 41%